2012
DOI: 10.1166/mex.2012.1067
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Free Hydrothermal Synthesis of Ag/C Nanocables

Abstract: A facile method is described here on synthesis of high-aspect-ratio Ag/C core/sheath nanocables via a hydrothermal process in the presence of Ag 2 S and in the absence of any surfactant or polymers. We demonstrate that glucose can act as a reducing reagent and provide carbon source to form a core-shell structure. The S 2− ion plays an important role in controlling the Ag + concentration and then the anisotropic growth of nanocables, and at the same time, the uncoated Ag particles get eroded and reused via Ag 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The 1D nanostructures of Ag/C have been developed so far with the help of some types of surfactant. In 2012, Mu et al showed the surfactant-free synthesis of 1D carbon-supported silver nanostructure with a high aspect ratio in the presence of glucose, which plays the role of carbon source [23]. For energy device applications basically, catalysts have been prepared in a powder form and mixed with a conducting polymer solution to get the catalyst ink.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1D nanostructures of Ag/C have been developed so far with the help of some types of surfactant. In 2012, Mu et al showed the surfactant-free synthesis of 1D carbon-supported silver nanostructure with a high aspect ratio in the presence of glucose, which plays the role of carbon source [23]. For energy device applications basically, catalysts have been prepared in a powder form and mixed with a conducting polymer solution to get the catalyst ink.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a resurrection of interest has come out to synthesize a carbon-supported silver catalyst. In our work, we have followed the synthesis method of Mu et al [23]. The motivation of our work was the surfactant-free synthesis of 1D carbon-supported silver nanostructures using hydrothermal conditions and studies their electrochemical characterization for borohydride oxidation in alkaline solution for the promising application in alkaline borohydride fuel cells and alcohol tolerance.…”
Section: Introductionmentioning
confidence: 99%